2019
DOI: 10.3382/ps/pez479
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding yeast bioactives to broiler breeders and/or their offspring on growth performance, gut development, and immune function in broiler chickens challenged with Eimeria

Abstract: Yeast bioactives (YB) may stimulate broiler breeders (BB) to increase deposition of immunoglobulins (Ig) in eggs. We investigated the effects of feeding YB (mixture of derivatives from whole yeast subjected to enzymatic hydrolysis) to BB and/or their offspring on growth performance, gut development, and immune function in broiler chickens challenged with Eimeria. The BB (Ross 708 ♀ and Ross ♂) were assigned to 2 groups (60 ♀ and 10 ♂) and fed basal or basal diet supplemented with 500 g of YB/Mt. A total of 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
1
36
0
3
Order By: Relevance
“…Thus, although E. acervulina and E. maxima challenge reduced jejunal mucosa IgA by 33% at 5 days post-challenge, the concentration was increased by 16% at 25 days post-challenge (86). A further study indicated that E. acervulina and E. maxima challenge increased jejunal IgA by 64% at 5 days post-challenge (149). Although specific mechanisms of action intestinal IgA on coccidial infections are still subject of investigations, it has been speculated that IgA reduces development of sporozoites or merozoites and prevent host cell invasion (150,151).…”
Section: Utility Of Yeast Cell Wall (Ycw) Components In Modulating Comentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, although E. acervulina and E. maxima challenge reduced jejunal mucosa IgA by 33% at 5 days post-challenge, the concentration was increased by 16% at 25 days post-challenge (86). A further study indicated that E. acervulina and E. maxima challenge increased jejunal IgA by 64% at 5 days post-challenge (149). Although specific mechanisms of action intestinal IgA on coccidial infections are still subject of investigations, it has been speculated that IgA reduces development of sporozoites or merozoites and prevent host cell invasion (150,151).…”
Section: Utility Of Yeast Cell Wall (Ycw) Components In Modulating Comentioning
confidence: 86%
“…These antibodies were highly protective, mediating up to a 97% reduction in oocyst shedding in challenged hatchlings. We recently showed that feeding broiler breeders yeast product rich in enzyme hydrolyzed cell wall components increased deposition of IgA in the hatching egg yolks (149). The data further indicated that feeding hydrolyzed yeast cell wall to broiler breeders and to the chicks improved jejunal histomorphology independent of Eimeria challenge (149).…”
Section: Utility Of Yeast Cell Wall (Ycw) Components In Modulating Comentioning
confidence: 96%
“…Moreover, YC also contains a large amount of trace elements, such as selenium and zinc that improve embryonic and early postnatal development of the aged layer (Hostetler et al, 2003;Sun et al, 2012). A previous study has shown that adding yeast bioactives significantly improves the level of IgA in the egg yolk (Lu et al, 2019), resulting in enhanced chick immunity and improved reproductive performance of the aged layers. Hens in the late laying stage are considered to be affected by oxidative stress and ovarian aging; furthermore, an increase in lipid and protein oxidation substantially influences the normal physiology of layers (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of YC at 2.5 g/kg activates macrophages, thereby increasing lysozyme content in the serum of laying hens, thus contributing to their resistance of pathogenic bacteria and enhancing their immunity (Gao et al, 2008). Further, studies have also reported that this immunity induced by YC is passed on to offspring and reduces symptoms of coccidiosis infection (Lu et al, 2019;Sun and Kim, 2019). In addition, some previous studies have shown that YC administration positively affects poultry laying performance and intestinal health (Zhang J.C. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation